2021
DOI: 10.1098/rspb.2021.1728
|View full text |Cite
|
Sign up to set email alerts
|

Linking cognition to ecology in wild sympatric mouse lemur species

Abstract: Cognitive abilities covary with both social and ecological factors across animal taxa. Ecological generalists have been attributed with enhanced cognitive abilities, but which specific ecological factors may have shaped the evolution of which specific cognitive abilities remains poorly known. To explore these links, we applied a cognitive test battery (two personality, ten cognitive tests; n = 1104 tests) to wild individuals of two sympatric mouse lemur species ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…After females emerged from hibernation, we retested the same individuals to assess memory retention of the learned stimulus–reward associations. We predicted no sex difference in learning of the association tasks before hibernation, as previously reported as part of another study (Henke‐von der Malsburg et al, 2021 ). Instead, considering the assumed reduced neurological processes during hibernation, we predicted variation in memory retention after hibernation in accordance with sex‐specific activity levels during the dry season.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…After females emerged from hibernation, we retested the same individuals to assess memory retention of the learned stimulus–reward associations. We predicted no sex difference in learning of the association tasks before hibernation, as previously reported as part of another study (Henke‐von der Malsburg et al, 2021 ). Instead, considering the assumed reduced neurological processes during hibernation, we predicted variation in memory retention after hibernation in accordance with sex‐specific activity levels during the dry season.…”
Section: Introductionsupporting
confidence: 77%
“…We briefly restrained newly captured individuals with .6 μl ketamine (50 mg/ml) per 1 g body mass to mark them with a subdermally implanted PIT tag (Trovan, Usling, Germany). We took standard morphometric measures, such as body mass, bizygomatic breadth, body and tail length, as well as tail circumference from all individuals that were captured for the first time in the respective field season (Eberle & Kappeler, 2002 ; Henke‐von der Malsburg et al, 2021 ). In addition to these targeted captures for experimental animals, we conducted monthly captures to assess population dynamics and general activity levels (Eberle & Kappeler, 2002 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A causality between cognition and tness is hard to determine, but several correlations have been found 2,4,54 suggesting that such a relationship exists. In addition to that, some studies found differences in cognition between populations or related species with different ecology that could be adaptive 38,59 .…”
Section: Evolution Cognitionmentioning
confidence: 99%